2017
DOI: 10.1007/5584_2017_2
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Rectal Ulcer Syndrome in Children: A Case Series Study

Abstract: Information on solitary rectal ulcer syndrome (SRUS) in children is limited and based on case reports only. This study was undertaken with the objective of describing the clinical history, symptoms, diagnostic work-up, and treatment of a large case series of pediatric patients with SRUS. The study was multi-center and retrospective. All pediatric endoscopists in Poland were invited to participate in the study and were asked to look through their endoscopic databases to identify SRUS cases from the last 10 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
3
6
1
1
Order By: Relevance
“…Clinical presentations of our study are almost similar to the previous studies by Kowalsk-Duplaga et al (15) of 31 children and Suresh et al ( 13) of 22 children. The main differences are the history of excessive straining during defecation which we were able to elicit in almost all cases and attempted manual evacuation of stool which was present in 50% of our cases while the figures were 45% to 64% and 19% to 27%, respectively, in previous studies (15,13). Recently, Dehghani et al (16) reported similar clinical features and colonoscopic findings in a study of 55 children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Clinical presentations of our study are almost similar to the previous studies by Kowalsk-Duplaga et al (15) of 31 children and Suresh et al ( 13) of 22 children. The main differences are the history of excessive straining during defecation which we were able to elicit in almost all cases and attempted manual evacuation of stool which was present in 50% of our cases while the figures were 45% to 64% and 19% to 27%, respectively, in previous studies (15,13). Recently, Dehghani et al (16) reported similar clinical features and colonoscopic findings in a study of 55 children.…”
Section: Discussionsupporting
confidence: 91%
“…Blackburn et al (18) showed a good response to behavioral modification alone in 7 of 8 children with SRUS. Kowalsk-Duplaga et al (15) used topical steroids in 19 of 31 children and showed healing (full or partial) in 14 (63.2%) cases. Dehghani et al (12) showed complete relief of symptoms in 7 (58.3%) of 12 children treated with sucralfate enema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent rectal bleeding and/or mucorrhea were the commonest presentation similar to other reported series (7,(11)(12)(13)(14)(15) Predisposing factors for SRUS like constipation (hard stool), straining during defecation were present in majority of case series (7,12,(14)(15)(16). The other presenting symptom which signifies rectal diseases like tenesmus, rectal prolapse were present in varying proportions (7,12,(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 76%
“…If neither a conservative method nor biofeedback is therapeutic, and if patients have a rectal prolapse or intussusception, surgical intervention may be considered such as ulcer excision or treatment of the rectal prolapse or rectal intus-susception [13]. If patients do not have a rectal prolapse or intussusception, but neither a conservative method nor biofeedback is therapeutic, local excision may be considered for symptomatic relief [15,16]. Both SRUS cases followed a conservative treatment plan where the former was treated with mesalamine, docusate, and increasing fiber intake.…”
Section: Discussionmentioning
confidence: 99%